The Broader Economic Value of School Feeding Programs in Low- and Middle-Income Countries: Estimating the Multi-Sectoral Returns to Public Health, Human Capital, Social Protection, and the Local Economy - Verguet, Stéphane; Limasalle, Paulina; Chakrabarti, Averi; Husain, Arif; Burbano, Carmen; Drake, Lesley; Bundy, Donald A. P. (Frontiers in Public Health, 2020)
Introduction: Globally, there are 370 million children receiving school meals every day. Coverage is least in low-income countries, where the need is greatest and where program costs are viewed as high in comparison with the benefits to public health alone. Here we explore the policy implications of including the returns of school feeding to other sectors in an economic analysis. Methods: We develop an economic evaluation methodology to estimate the costs and benefits of school feeding programs across four sectors: health and nutrition; education; social protection; and the local agricultural economy. We then apply this multi-sectoral benefit-cost analytical framework to school feeding programs in 14 countries (Botswana, Brazil, Cape Verde, Chile, Côte d'Ivoire, Ecuador, Ghana, India, Kenya, Mali, Mexico, Namibia, Nigeria, and South Africa) for which input data are readily available. Results: Across the 14 countries, we estimate that 190 million schoolchildren benefit from school feeding programs, with total program budgets reaching USD11 billion per year. Estimated annual human capital returns are USD180 billion: USD24 billion from health and nutrition gains, and USD156 billion from education. In addition, school feeding programs offer annual social protection benefits of USD7 billion and gains to local agricultural economies worth USD23 billion. Conclusions: This multi-sectoral analysis suggests that the overall benefits of school feeding are several times greater than the returns to public health alone, and that the overall benefit-cost ratio of school feeding programs could vary between 7 and 35, with particular sensitivity to the value of local wages. The scale of the findings suggests that school feeding programs are potentially much more cost-beneficial when viewed from the perspective of their multi-sectoral returns, and that it would be worthwhile following up with more detailed analyses at the national level to enhance the precision of these estimates.